SAT0455 Impact of psoriatic arthritis in the workplace: results of the french survey psopro. (15th June 2017) - Claudepierre, P; Bonnet, I; Roquelaure, Y; Levy, P; Aubert, R; Bachelez, H
Abstract : Objectives: The PsoPRO (Psoriasis & PROfessional life) survey, run under the aegis of the patient advocacy groups France Psoriasis, was aimed at measuring, in comparison to the general population, the impacts of psoriasis occurring alone (PsO) or concurring with psoriatic arthritis (PsO+PsA) on patients' working life. Methods: From 13/07/16 to 08/08/16, 714 PsO patients, 81 of whom were under systemic treatment (PsO-ST), and 84 patients PsO+PsA were surveyed using a questionnaire drawn up by a multi-disciplinary scientific committee and conducted via the Internet. In addition to medical and professional characteristics, patients provided their recent absenteeism and presenteeism data, using a WPAI-PSO standardized self-questionnaire, as well as information about the interactions between psoriasis and their working life. Using the Student, Chi-deux and Fischer tests, patients were compared with a sample of 604 working respondents representative of the French population and questioned about the impact of possible health problems on their working life. Results: The socio-demographic characteristics of the control group were similar to those of the total patient population with psoriasis, although men were slightly over-represented in the latter group. The duration of disease and cutaneous and rheumatismal locations were in line with those usually found in the literature. The unemployment rate over the previous 5 years and number of days of medical leave over the previous 12 months was higher in the PsO+PsA group as compared to the control group (Table 1 ). In the sub-group reporting a flare-up at the time of the survey, the impact of the disease on absenteeism, presenteeism and productivity was significantly higher in PsO-ST and PsO+PsA patients (Figure 1 ). Despite this, PsO-ST and PsO+PsA patients reported greater attachment to their work than did those in the control group (Table 1 ). Conclusions: In patients with PsO, placement under systemic treatment or the co-existence of PsA appears to be associated with greater impact on patients' working life, though they also reported higher attachment to their work. Close supervision and appropriate care in PSO patients developing PsA should limit these impacts. Acknowledgements: This survey was made possible by funding from Celgene France and participation of the patient advocacy groups France Psoriasis. Disclosure of Interest: P. CLAUDEPIERRE Grant/research support from: AbbVie, MSD, Roche, Pfizer, Consultant for: AbbVie, BMS, Celgene, Janssen, MSD, Novartis, Pfizer, Roche, UCB, I. BONNET: None declared, Y. ROQUELAURE Consultant for: Abbott, Celgene, P. LEVY Consultant for: AbbVie, Actelion, Amgen, Anergis, Astellas, Bayer, Becton Dickinson, Biogen, BMS, Conceptus, Daïchi-Sankyo, Eli Lilly, EOS, Gilead, GSK, Hospira, Impeto Médical, Janssen, MSD, Mundipharma, Novartis, Novo Nordisk, Roche, Sanofi Pasteur MSD, Stallergènes. H., R. AUBERT: None declared, H. BACHELEZ Grant/research support from: Pfizer, Consultant for: Abbvie, Actelion, Amgen, Boehringer, Celgene, Eli- Lilly, Janssen, Leo Pharma, Novartis, Pfizer, Takeda, Abbott, Merck Serono, Roche, Schering-Plough, Wyeth